2017
DOI: 10.18632/oncotarget.23050
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA protein activates Akt and attenuates chemotherapeutics-induced apoptosis in gastric cancer cells

Abstract: Infection with cagA-positive Helicobacter pylori is associated with a higher risk of gastric cancer. The cagA gene product, CagA, is translocated into gastric epithelial cells and perturbs host cellular biological functions. Etoposide, a topoisomerase II inhibitor widely used to couple DNA damage to apoptosis, is a common cytotoxic agent used for advanced gastric cancer. We investigate the effect of CagA on etoposide-induced apoptosis in gastric cancer cells to elucidate whether CagA play a role in gastric car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…47,48 Previous results presented that etoposide boosted the phosphorylation of Akt while minimizing cell survival via the induction of GC apoptosis. 49 It was shown that the abnormal methylation in PTEN promoter was substantially reduced in Uyghur subjects suffering from mild cases of T2DM. It was further shown that the hypomethylation in PTEN promoter was pretty common in T2DM subjects, indicating that PTEN might contribute to T2DM pathogenesis among Uyghur people.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Previous results presented that etoposide boosted the phosphorylation of Akt while minimizing cell survival via the induction of GC apoptosis. 49 It was shown that the abnormal methylation in PTEN promoter was substantially reduced in Uyghur subjects suffering from mild cases of T2DM. It was further shown that the hypomethylation in PTEN promoter was pretty common in T2DM subjects, indicating that PTEN might contribute to T2DM pathogenesis among Uyghur people.…”
Section: Discussionmentioning
confidence: 99%
“…Recently studies illustrated the Helicobacter pylori CagA protein activates Akt pathway and desensitizes etoposide, another cytotoxic agent for treatment of advanced gastric cancer, 22 indicating CagA promotes glycolysis could through activation of Akt. To further investigate the underlying molecular mechanism of the CagA-promoted glucose metabolism, we examined Akt pathway in CagA positive gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the molecular mechanisms of the CagA-promoted glycolysis, we examined the phosphorylation of Akt since it has been reported that activation of Akt pathway contributed to the glycolysis upregulation. 22 Expectedly, overexpression of CagA promoted the phosphorylation of Akt. Thus, we treated gastric cancer cells with Akt inhibitor and found inhibition of Akt significantly blocked the CagA-upregulated cellular glycolysis, suggesting blocking glycolysis by either Akt inhibitor or glycolysis inhibitor could enhance the cytotoxicity of 5-Fu.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, activation of PI3K/AKT and ERK/JNK pathways, which leads to increased cell growth and survival and induction EMT as well as increased cell motility, respectively [ 60 , 146 ], has been observed in both EBV- and H. pylori -associated GC. In case of EBV, its oncoprotein LMP2A is responsible for these activations, which has been confirmed in both in vitro and in an in vivo transgenic mouse model [ 146 , 154 , 155 , 156 ], while CagA is the primary virulence factor of H. pylori that activates these pathways [ 142 , 146 , 157 , 158 , 159 , 160 ].…”
Section: Gastric Cancermentioning
confidence: 96%